Utilization and factors associated with antenatal, delivery and postnatal Care Services in Tigray Region, Ethiopia: a community-based cross-sectional study - Mussie Alemayehu; Tesfay Gebregzabher Gebrehiwot; Araya Abrha Medhanyie; Alem Desta; Tesfu Alemu; Atakelti Abrha; Hagos Godefy (BMC, 2020)
Abstract Background This study aimed to identify the utilization and factors associated with antenatal care, delivery, and postnatal care services in Tigray regional state, Ethiopia. Methods A community-based cross-sectional study was conducted among 667 women of reproductive age group who had children aged 45 days - 6 months in 13 districts (3 urban and 10 rural). Data were collected from May-June 2015. Multistage sampling technique was used. The data were analyzed using SPSS version 20. Multiple variable logistic regression analysis was used to identify the factors associated with the utilization of antenatal care, institutional delivery, and postnatal care services. Results Of the total, the proportion of women who visited a health facility for antenatal care four or more times (ANC 4+) was 58.2%, those who chose institutional delivery was 87.9%, and those who received postnatal care (PNC) within 42 days of birth at least once was 40.3%. Residing in an urban area, having an electronic media, and having 2-5 children were factors associated with an ANC 4+ visit. Whereas, partner involvement in ANC visit (AOR = 2.4, 95% of CI: 1.37, 4.35) and content of ANC discussed (AOR = 4.0, 95% of CI: 1.08, 14.93), having birth preparedness (AOR = 2.6, 95% of CI: 1.44, 4.97), residing within a distance of less than a 30-min walk to the nearest health facility (AOR = 2.0, 95% of CI: 1.16, 3.64), and having ANC 4+ visits (AOR = 2.4, 95% of CI: 1.39, 4.31) were the factors that were found to be associated with institutional delivery. As regards to PNC visits within 42 days of birth, age of 40-45 years, having 2-5 children, and ANC 4+ visits were found to be significant factors associated with it. Conclusion The proportion of women who attended antenatal care and gave birth in a health facility was high. However, the proportion of women who attended antenatal and postnatal care was low. Residing in urban areas, having an electronic media, living near a health facility, having partner involvement in decision making, receiving appropriate ANC counseling, having birth preparedness, age of the woman, and number of children could potentially influence maternal health services utilization.